Modified polyvinylidene fluoride lithium-sulfur battery positive electrode binder and preparation method thereof

By dissolving and drying the PVDF powder and the modifier in an organic solvent, the positive electrode binder of the modified PVDF lithium sulfur battery was constructed, which solved the problem of poor cycle stability caused by the "shuttle effect" of lithium polysulfide in the lithium sulfur battery and the volume change of the sulfur positive electrode, and achieved higher mechanical properties and cycle stability.

CN119823675AActive Publication Date: 2025-04-15SOUTHWEST PETROLEUM UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510107901.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The "shuttle effect" of lithium polysulfide in lithium sulfur batteries and the huge volume changes in the sulfur positive electrode during charging and discharging lead to loss of active substances and damage to electrode integrity, resulting in poor cycling stability. The existing PVDF binders have low bond strength to sulfur, poor ductility, and lack functional groups that inhibit the "shuttle effect".

Method used

Preparation is made by dissolving and drying the PVDF powder and a modifier such as ferrocene boric acid in an organic solvent, and then a modified PVDF lithium-sulfur battery positive electrode binder is constructed. The modifier improves the mechanical properties of the binder by forming hydrogen bonds and cross-linking with the PVDF molecular chain, and has affinity for lithium ions through the ring-cross ring, inhibiting the shuttle of LiPSs.

Benefits of technology

Modified PVDF binder can effectively improve the mechanical properties and cycle stability of sulfur cathode, inhibit the shuttle of LiPSs, extend the cycle life of lithium sulfur batteries, and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823675A_ABST
    Figure CN119823675A_ABST
Patent Text Reader

Abstract

The invention discloses a modified polyvinylidene fluoride lithium-sulfur battery positive electrode binder and a preparation method thereof, and belongs to the technical field of lithium-sulfur batteries. According to the method, the modifier is connected with a polyvinylidene fluoride molecular chain through a hydrogen bond, so that crosslinking of the polyvinylidene fluoride molecular chain is realized, and the mechanical property of the polyvinylidene fluoride binder is improved; due to the introduction of the modifier, the crystallinity of the polyvinylidene fluoride is reduced, the porosity is increased, the swelling of the polyvinylidene fluoride binder in an electrolyte is promoted, and the lithium ion conductivity is increased; meanwhile, a cyclopentadienyl ring connected with an iron atom in the modifier not only provides an adsorption site of the lithium polysulfide, but also can promote the conversion of the lithium polysulfide. The modified polyvinylidene fluoride binder obtained by the method is simple in synthesis process and low in cost, can remarkably reduce polarization of a sulfur positive electrode and improve the cycling stability and rate capability of the battery when being applied to the positive electrode of the lithium-sulfur battery, and is suitable for a traditional lithium battery electrode preparation process and suitable for large-scale commercial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-sulfur batteries, and particularly relates to a modified polyvinylidene fluoride lithium-sulfur battery positive electrode binder which can improve the adsorption of lithium polysulfides in lithium-sulfur batteries, promote the conversion of lithium polysulfides and has good mechanical properties, and a preparation method thereof. Background Art

[0002] Lithium-sulfur batteries have the characteristics of high theoretical energy density, low cost, and environmental friendliness, and are regarded as the next generation of secondary battery systems after existing commercial lithium-ion batteries. However, lithium-sulfur batteries face multiple technical challenges before practical application. On the positive electrode side, the "shuttle effect" of lithium polysulfides (LiPSs) and the huge volume change of the sulfur positive electrode during charging and discharging lead to the loss of active materials and the destruction of electrode integrity, which makes the cycle stability of lithium-sulfur batteries very poor.

[0003] Polyvinylidene fluoride (PVDF) has the advantages of good electrochemical stability and thermal stability, and is the most commonly used electrode binder in commercial lithium-ion batteries. However, PVDF is not suitable for lithium-sulfur battery cathodes for the following reasons: First, its bonding strength to sulfur is low, its ductility is poor, and it is difficult to maintain the integrity of the sulfur cathode, especially at high sulfur loadings; second, PVDF lacks functional groups that are pro-LiPSs and cannot play a role in inhibiting the "shuttle effect"; third, electronic and lithium ion insulation will increase the polarization of the electrode. Therefore, it is very necessary to modify PVDF to improve its mechanical properties and give it the adsorption and catalytic conversion effect on LiPSs.

[0004] In the prior art, the modification of PVDF-based binders mainly adopts copolymerization, grafting and other methods. For example, Chinese invention patent CN112175127A discloses a copolymerized PVDF resin for lithium battery binder, which improves the bonding performance of PVDF resin to positive electrode active materials and current collectors. For example, Chinese invention patent CN117089298A discloses a cross-linked polyvinylidene fluoride binder and its preparation method and an electrode using the cross-linked polyvinylidene fluoride binder. Compared with ordinary PVDF binders, the binder has stronger mechanical strength and toughness, can buffer the stress generated by the volume change of active materials during the battery charge and discharge cycle, and enhance the overall strength of the electrode; the adhesion between the current collector is stronger, preventing the occurrence of active material breakage, peeling and other phenomena; and also improves the conductivity of the battery using the binder. For example, Chinese invention patent CN117625093A discloses a PVDF-based graft copolymer type lithium-sulfur battery binder and its preparation method and application. The polycation structure introduced on the main chain of polyvinylidene fluoride-based material has an adsorption effect on polysulfides produced during the electrochemical reaction of lithium-sulfur batteries, which can inhibit the loss of positive electrode active substances and improve the cycle stability of lithium-sulfur batteries; the bistrifluoromethylsulfonyl imide anion group coordinated by the cationic main chain is conducive to the transmission of lithium ions in the positive electrode and improves the ionic conductivity of the positive electrode; the binder structure with branched chains has better adhesion and can prevent the positive electrode active substances from falling off. However, the common disadvantage of the above technologies is that the preparation process of the modified PVDF binder is complicated and the production cost is high. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a modified polyvinylidene fluoride (PVDF) binder for lithium-sulfur battery positive electrode. Compared with the unmodified PVDF binder, the binder can improve the ability of the sulfur positive electrode to resist volume changes during charging and discharging, especially under high sulfur loading conditions, so that the sulfur positive electrode material can be firmly adhered to the current collector, and can effectively accelerate the LiPSs conversion reaction in the lithium-sulfur battery, greatly inhibit the shuttle of soluble LiPSs, and improve the long-cycle stability of the battery.

[0006] The present invention also provides a method for preparing the modified PVDF lithium-sulfur battery positive electrode binder. The method uses commercial PVDF powder as a raw material, does not need to change the existing PVDF powder preparation process, and the modifier is directly added to the electrode slurry as an additive. The operation is simple, the process is controllable, the production cost is low, and it can be well compatible with the existing lithium-ion battery electrode preparation process, so it has a good prospect for industrial promotion and application.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.

[0008] The invention prepares the modified PVDF binder by dissolving PVDF powder and a modifier in an organic solvent according to a certain mass ratio and then drying the organic solvent.

[0009] A modified PVDF lithium-sulfur battery positive electrode binder, wherein the binder matrix is ​​commercial PVDF powder, the modifier is one or more of ferrocenylboric acid, ferrocenyldiboric acid, ferrocenyldicarboxylic acid, ferrocenyl dimethanol, and diaminoferrocene, and the organic solvent is N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), or a mixture of the two.

[0010] A method for preparing a modified PVDF lithium-sulfur battery positive electrode binder comprises the following steps in sequence: (1) Adding PVDF powder and modifier into an organic solvent in a certain mass ratio, stirring and dissolving to obtain a mixed solution of PVDF and modifier; (2) The modified PVDF lithium-sulfur battery positive electrode binder is obtained by drying the organic solvent in the mixed solution obtained in step (1).

[0011] Furthermore, in the step (1), the mass ratio of PVDF powder to modifier is 1: 0.05-0.25. Too little modifier will result in too little hydrogen bonding between the modifier and PVDF, resulting in no obvious improvement in mechanical properties, while too much modifier will lead to a decrease in the adhesion and electrochemical stability of PVDF itself.

[0012] Furthermore, in the step (1), the stirring and dissolving time is 8 to 24 hours, preferably 12 to 16 hours.

[0013] Furthermore, in the step (2), the drying temperature is 60-150°C, preferably 80-120°C.

[0014] The mechanism of the present invention is as follows: The hydroxyl, carboxyl, amino and other groups in the modifier molecules can generate hydrogen bonds with fluorine atoms on different molecular chains of PVDF, thereby evenly anchoring the modifier molecules on the PVDF molecular chains and causing cross-linking between PVDF molecular chains; the cyclopentadienyl in the modifier molecules has a strong affinity for lithium ions, which is beneficial to inhibit the shuttling of LiPSs and reduce the energy barrier of the reaction conversion step. To this end, the present invention rationally constructs a modified PVDF lithium-sulfur battery positive electrode binder, aiming to improve the mechanical properties of the PVDF binder, accelerate the process of LiPSs conversion in the lithium-sulfur battery positive electrode and stabilize the positive electrode structure, so as to achieve excellent cycle performance of the lithium-sulfur battery.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The modified PVDF lithium-sulfur battery positive electrode binder constructed by the present invention can well maintain the integrity of the positive electrode during the battery charging and discharging process, and exhibits good adsorption and catalytic conversion effects on soluble LiPSs, thereby improving the cycle stability of the lithium-sulfur battery; Compared with other types of cross-linked organic polymer binders, the binder obtained by this method has better electrochemical stability, more excellent catalytic activity and lower production cost; This method is compatible with existing lithium-ion battery electrode preparation processes and is easy to implement on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the X-ray photoelectron spectrum of the modified PVDF binder prepared in Example 1; Figure 2 is the Fourier transform infrared spectrum of the modified PVDF binder prepared in Example 1; Figure 3 It is the grazing incidence X-ray diffraction pattern of the binder prepared in Examples 1 to 3 and Comparative Example 1; Figure 4 It is a bar graph of the Young's modulus of the adhesives prepared in Examples 1 to 3 and Comparative Example 1; Figure 5 The figure is a comparison of the cycle performance of the binders prepared in Example 1 and Comparative Example 1 in a lithium-sulfur pool; Figure 6 Comparison of charge and discharge curves of the binders prepared in Examples 1 to 3 and Comparative Example 1 in lithium-sulfur batteries; Figure 7 The figure is a comparison of the rate performance of the binders prepared in Examples 1 to 3 and Comparative Example 1 in lithium-sulfur batteries. DETAILED DESCRIPTION

[0017] The following is a clear and complete description of the technical solution of the present invention in conjunction with the accompanying drawings and embodiments, and the described embodiments do not limit the present invention. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention.

[0018] Unless otherwise specified, the experimental instruments and drugs described below can be obtained from commercial channels.

[0019] Example 1: A PVDF lithium-sulfur battery positive electrode binder modified with ferrocene diboric acid (FcBA) is prepared by the following steps: (1) 80 mg of FcBA powder and 320 mg of PVDF powder were dissolved in 9.6 g of NMP and stirred for 12 h to obtain a mixed NMP solution of PVDF and FcBA with a solute mass of 4%; (2) The solution obtained in step (1) is dried at 100° C. to obtain a modified PVDF binder with a FcBA mass fraction of 20%.

[0020] Example 2: The difference between Example 2 and Example 1 is that in step (1), the amount of FcBA used is 20 mg and the amount of PVDF powder used is 380 mg; in step (2), a modified PVDF binder with a FcBA mass fraction of 5% is obtained.

[0021] Example 3: The difference between Example 3 and Example 1 is that in step (1), the amount of FcBA used is 40 mg and the amount of PVDF powder used is 360 mg; in step (2), a modified PVDF binder with a FcBA mass fraction of 10% is obtained.

[0022] Comparative Example 1: Unmodified PVDF binder was prepared by the following steps: (1) Dissolve 400 mg of PVDF powder in 9.6 g of NMP and stir for 12 h to obtain a 4% PVDF NMP solution; (2) The solution obtained in step (1) is dried at 100° C. to obtain an unmodified PVDF binder.

[0023] The following is a performance analysis of the binders prepared in Examples 1 to 3 and Comparative Example 1: Figure 1 Figure 3 is the X-ray photoelectron spectrum of the modified PVDF binder with a FcBA mass fraction of 20% in Example 1. It can be found in the figure that a new peak appears at the 292.4 eV position of the C 1s spectrum of Example 1. This is because FcBA is dispersed in multiple groups of linearly arranged molecular chains of PVDF, resulting in the F atoms in the local PVDF molecular chains being unable to face the H atoms in the previously arranged molecular chains, resulting in an increase in the binding energy of the local C chain. Similarly, a new peak is found at the 688.3 eV position of the F 1s spectrum, which is consistent with the result of C 1s, and the peak binding energy is reduced at 687.28 eV, which is due to the hydrogen bond between the CF chain and FcB.

[0024] Figure 2 The Fourier transform infrared spectrum of the modified PVDF binder with a mass fraction of FcBA of 20% in Example 1 can be seen from the figure that the PVDF-FcB binder film has a wavelength of 3250-3500 cm -1 The vibration contraction of OH causes the absorption peak to become broader and shift to the right compared with that of pure FcB powder, indicating that there is a hydrogen bond between PVDF and FcB molecular chains. The corresponding 1230-1400 cm -1The FCF absorption peak intensity is significantly lower than that of pure PVDF powder, indicating that the FCF dipole moment is reduced, which is also caused by the formation of hydrogen bonds between PVDF and FcBA molecules.

[0025] Figure 3 3 are grazing incidence X-ray diffraction patterns of the binders prepared in Examples 1 to 3 and Comparative Example 1. It can be found in the figure that the diffraction peaks of the modified PVDF binders in Examples 1 to 3 match those of the unmodified PVDF binder in Comparative Example 1, and with the increase of the content of the FcBA additive, the diffraction peak intensities of the (100), (020), (110) and (021) planes of PVDF are continuously decreasing, indicating that the addition of FcBA reduces the crystallinity of PVDF, increases the porosity, and can promote the absorption of the electrolyte by the PVDF binder.

[0026] Figure 4 It is a bar graph of the Young's modulus of the binders prepared in Examples 1 to 3 and Comparative Example 1. It can be seen from the figure that the average Young's modulus of the unmodified PVDF binder in Comparative Example 1 is only 0.45 GPa, while the average Young's modulus of the modified PVDF binder with a FcBA mass fraction of 20% in Example 1 can reach 2.12 GPa, indicating that the modified PVDF binder has higher toughness and mechanical properties, which is beneficial to buffering the volume expansion of the high-load sulfur positive electrode and reducing the shedding of the positive electrode material during the cycle.

[0027] Figure 5 By comparing the cycle performance of the binders prepared in Example 1 and Comparative Example 1 in lithium-sulfur batteries, it can be seen that after a long cycle of 600 cycles at a current density of 2C, the battery using the binder in Example 1 exhibits excellent cycle stability, and the capacity retention rate is above 83%, and the coulombic efficiency is maintained at around 98.5%, indicating that the modified binder has excellent chemical stability in the battery and the sulfur positive electrode maintains better integrity; while the battery using the unmodified PVDF binder in Comparative Example 1 exhibits low capacity and decreasing coulombic efficiency in long cycles, which may be due to the continuous shuttling and accumulation of LiPSs or the corrosion of the negative electrode metal lithium.

[0028] Figure 6 The charge and discharge curves of the binders prepared in Examples 1 to 3 and Comparative Example 1 in lithium-sulfur batteries are compared. It can be seen from the figure that the battery using the modified PVDF binder with an FcBA content of 20% in Example 1 has the lowest voltage polarization.

[0029] Figure 7The rate curves of the binders prepared in Examples 1 to 3 and Comparative Example 1 in lithium-sulfur batteries show that when the current density is 0.2C to 3C, the battery capacity using the modified PVDF binder with an FcBA content of 20% in Example 1 is the highest, regardless of whether the current density is small or large, showing good rate performance.

Claims

1. A method for preparing a modified polyvinylidene fluoride lithium-sulfur battery positive electrode binder, characterized in that: The following steps are involved: (1) adding polyvinylidene fluoride powder and a modifier into an organic solvent in a certain mass ratio, stirring and dissolving to obtain a mixed solution of polyvinylidene fluoride and the modifier; (2) The organic solvent in the mixed solution obtained in step (1) is dried to obtain the modified polyvinylidene fluoride lithium-sulfur battery positive electrode binder.

2. The method for preparing the modified polyvinylidene fluoride lithium-sulfur battery positive electrode binder according to claim 1, characterized in that: The modifier described in step (1) is one or more of ferroceneboric acid, ferrocendiboric acid, ferrocendicarboxylic acid, ferrocenedimethanol, and diaminoferrocene.

3. The method for preparing the modified polyvinylidene fluoride lithium-sulfur battery positive electrode binder according to claim 1, characterized in that: The mass ratio of the polyvinylidene fluoride powder to the modifier in step (1) is 1: 0.05-0.

25.

4. The method for preparing the modified polyvinylidene fluoride lithium-sulfur battery positive electrode binder according to claim 1, characterized in that: The organic solvent in step (1) is N-methylpyrrolidone (NMP) or N,N-dimethylformamide (DMF) or a mixture of the two.

5. A modified polyvinylidene fluoride lithium-sulfur battery positive electrode binder prepared according to any one of the preparation methods of claims 1 to 4.

Citation Information

Patent Citations

  • Copolymerized PVDF resin for lithium battery binder

    CN112175127A

  • Crosslinked polyvinylidene fluoride binder, preparation method thereof and electrode

    CN117089298A

  • PVDF (Polyvinylidene Fluoride)-based polyelectrolyte type lithium-sulfur battery binder as well as preparation method and application thereof

    CN117625093A

  • Nitrogen-containing binder for sulfur-lithium batteries and preparation method thereof

    CN106159272A

  • Positive electrode mixture, positive electrode, and secondary battery

    CN117223123A